Homozygous PPT1 Splice Donor Mutation in a Cane Corso Dog With Neuronal Ceroid Lipofuscinosis. (23rd December 2016) - Kolicheski, A.; Barnes Heller, H.L.; Arnold, S.; Schnabel, R.D.; Taylor, J.F.; Knox, C.A.; Mhlanga‐Mutangadura, T.; O'Brien, D.P.; Johnson, G.S.; Dreyfus, J.; Katz, M.L.
Abstract : A 10‐month‐old spayed female Cane Corso dog was evaluated after a 2‐month history of progressive blindness, ataxia, and lethargy. Neurologic examination abnormalities indicated a multifocal lesion with primarily cerebral and cerebellar signs. Clinical worsening resulted in humane euthanasia. On necropsy, there was marked astrogliosis throughout white matter tracts of the cerebrum, most prominently in the corpus callosum. In the cerebral cortex and midbrain, most neurons contained large amounts of autofluorescent storage material in the perinuclear area of the cells. Cerebellar storage material was present in the Purkinje cells, granular cell layer, and perinuclear regions of neurons in the deep nuclei. Neuronal ceroid lipofuscinosis (NCL) was diagnosed. Whole genome sequencing identified a PPT1c.124 + 1G>A splice donor mutation. This nonreference assembly allele was homozygous in the affected dog, has not previously been reported in dbSNP, and was absent from the whole genome sequences of 45 control dogs and 31 unaffected Cane Corsos. Our findings indicate a novel mutation causing the CLN1 form of NCL in a previously unreported dog breed. A canine model for CLN1 disease could provide an opportunity for therapeutic advancement, benefiting both humans and dogs with this disorder.